2008
DOI: 10.1016/j.ceca.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic regulation of endogenous TRPM2 channels by adenine dinucleotides in primary human neutrophils

Abstract: SummaryThe Ca 2+ -permeable TRPM2 channel is a dual function protein that is activated by intracellular ADPR through its enzymatic pyrophosphatase domain with Ca 2+ acting as a co-factor. Other TRPM2 regulators include cADPR, NAADP and H 2 O 2 , which synergize with ADPR to potentiate TRPM2 activation. Although TRPM2 has been thoroughly characterized in overexpression or cell-line systems, little is known about the features of TRPM2 in primary cells. We here characterize the regulation of TRPM2 activation in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 42 publications
3
103
3
Order By: Relevance
“…Furthermore, it is of interest to observe that the location of NAADP production by CD38 appears to be distinct from that of cADPR synthesis; cADPR production is predominantly in early endosomes (45), whereas NAADP is produced mainly in lysosome-related acidic organelles (Ref. 38 and Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is of interest to observe that the location of NAADP production by CD38 appears to be distinct from that of cADPR synthesis; cADPR production is predominantly in early endosomes (45), whereas NAADP is produced mainly in lysosome-related acidic organelles (Ref. 38 and Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not find any significant signals with high concentration of the nucleotides (data not shown). It was reported that NAADP-mediated Ca 2ϩ influx is triggered from the TRPM2 channel (38). To determine the role of TRPM2 on IL-8-induced Ca 2ϩ signaling, we measured the change in [Ca 2ϩ ] i in the presence of ACA, a specific TRPM2 channel blocker.…”
Section: Naadp Releases Ca 2ϩ From Lysosome-like Acidic Organelles Inmentioning
confidence: 99%
“…Transient receptor potential melastatin 2 (TRPM2) is a thermosensitive, Ca 2+ -permeable cation channel expressed by a wide range of immunocytes, including macrophages, whose function is gradually being clarified (3)(4)(5)(6)(7)(8)(9). We previously reported that heat stimulation activates TRPM2 in the presence of low concentrations of agonists, such as adenosine diphosphate ribose (ADPR) and related molecules (10).…”
Section: Calcium | Immune Cellsmentioning
confidence: 99%
“…Of note, TRPM2 is expressed by lymphocytes, neutrophils, and monocytes/macrophages (3)(4)(5)(6)(7)(8), whose activities have a strong relationship with body temperature (2,41). This suggests that TRPM2 might have a broader role in the temperature sensitivity of the immune system.…”
Section: 5°c (Student T Test)mentioning
confidence: 99%
“…Accumulating evidence show that members of TRPC could be activated by diacylglycerol (Bréchard et al, 2008;. In addition, cyclic adenosine diphosphoribose, via its hydrolysis product (adenosine diphosphoribose), could support Ca 2+ entry through the activation of TRPM2, a member of transient receptor potential family (Heiner et al, 2006;Howard et al, 1993;Lange et al, 2008).…”
Section: Non-store-operated Camentioning
confidence: 99%